Islamic banking sectors in Gulf Cooperative Council countries: analysis on revenue, cost and profit efficiency concepts - Kamarudin, Fakarudin; Md Nassir, Annuar; Yahya, Mohamed Hisham; Mohd Said, Ridzwana; Amin Noordin, Bany Ariffin (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2014)
This paper examines the revenue efficiency and the others efficiencies concepts profit and cost efficiency levels of 74 banks (47 conventional and 27 Islamic banks) in Gulf Cooperative Council (GCC) countries over the periods 2007 to 2011. The level of efficiencies was measured using Data Envelopment Analysis (DEA) method which applied the intermediation approach. We find that, that the Islamic banks have exhibited a lower efficiency levels for all three efficiencies measures rather than conventional banks. This study seems to suggest revenue efficiency seems to play the main factor leading to the lower or higher profit efficiency levels. The determinants that could improve the revenue efficiency in GCC Islamic banks were identified using Multiple Regression Analysis (MRA). Four bank specific determinants were found to influence the improvement of revenue efficiency: asset quality, non-traditional activities, management quality and liquidity. The improvement of the revenue efficiency in GCC Islamic banks was also influenced by the macroeconomic variable inflation and concentration ratio of the three largest banks.